OP0191 Prophylaxis for the Prevention of Obstetric Complications in Asymptomatic Women with Antiphospholipid Antibodies. (9th June 2015) - Amengual, O.; Fujita, D.; Otta, E.; Carmona, L.; Kenji, O.; Sugiura-Ogasawara, M.; Murashima, A.; Atsumi, T.
Abstract : Background: The occurrence of recurrent thrombotic events and/or of obstetric complications in association with the persitence of antiphospholipid antibodies (aPL) defines the antiphospholipid syndrome (APS). Positive aPL can be recognized through the screening of otherwise asymptomatic pregnancies, however, the effect of aPL in the pregnancy outcomes of asymptomatic aPL carriers is uncertain. Objectives: To evaluate whether primary prophylaxis would be beneficial to prevent obstetric complications in asymptomatic women positive for aPL who have no history of clinical manifestations of APS. Methods: We performed a systematic review of the literature. Studies evaluating the effect of prophylactic treatment vs. no treatment in asymptomatic pregnant aPL carriers were identified in an electronic database search. The literature search was performed in the major databases: Medline from 1950 via PubMed, Embase, and the Cochrane Central Register of Controlled Trials. Conference abstracts of six major international conferences were searched from January 2012 to July 2014 on their official webpages. Design, population, and outcome homogeneity of studies were assessed and meta-analysed. Risk of bias was assessed through an ad hoc checklist. The pooled Mantel-Haenszel relative risk (RR) and 95% confidence interval (CI) of specific pregnancy outcomes were obtained using random effects models. Heterogeneity was measured with the I 2 statistic. All analyses were conducted in Review Manager 5.3. Results: Data from five studies with moderate to low risk of bias involving 154 pregnancies were included and three studies were meta-analysed. The RR of live birth rates, preterm birth, low birth weight and overall pregnancy complications in treated vs. un-treated pregnancies were 1.14 [0.18-7.31]; 1.71 [0.32 - 8.98]; 0.98; [0.07 -13.54] and 2.15 [0.63-7.33], respectively. Results from the meta-analysis could not prove that treatment with aspirin was superior to placebo to prevent pregnancy complications in asymptomatic aPL carriers. Conclusion: This systematic review did not find evidence of the superiority of prophylactic treatment with aspirin compared to placebo or to usual care for preventing unfavourable obstetric outcomes in otherwise healthy women with aPL during the first pregnancy. Disclosure of Interest: O. Amengual: None declared, D. Fujita: None declared, E. Otta: None declared, L. Carmona: None declared, O. Kenji: None declared, M. Sugiura-Ogasawara: None declared, A. Murashima: None declared, T. Atsumi Grant/research support from: Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Bristol-Myers Squibb Co., Astellas Pharma Inc., Daiichi Sankyo Co., Ltd. and Mitsubishi Tanabe Pharma Co., Speakers bureau: Astellas Pharma Inc. and Mitsubishi Tanabe Pharma Co.